Penafsiran QS Ali Imran: 159 dan Asy-Syura: 38 tentang Musyawarah dan Sistem Pengambilan - Zulfian Achmad Noviandi; Hafija Safarina; Muhammad Rizaldy Firdaus (Indo Publishing, 2026)
Musyawarah (deliberation) is a fundamental principle in Islam emphasized in the Qur’an as a collective decision-making process that ensures justice and wisdom. This study aims to analyze the interpretation of QS Ali Imran:159 and QS Asy-Syura:38 regarding musyawarah and its application in contemporary Islamic governance. Using qualitative library research, the study reviews classical and modern tafsir literature to explore how musyawarah fosters ethical, inclusive, and effective decision-making. Findings reveal that musyawarah serves not only as a dialogue method but also as a manifestation of faith, promoting social cohesion and accountability. The research highlights the continued relevance of musyawarah for addressing modern socio-political challenges in Muslim communities. The study concludes that musyawarah remains essential for just governance, balancing rational, spiritual, and social dimensions in Islamic leadership.